화옹간척지 밭조성 사업의 경제성 분석 - 신용광 (한국농촌경제연구원, 2008)
The purposes of this study are to assess the needs for farming in a reclaimed land and to suggest the directions for establishing upland fields in the reclaimed land, considering changing agricultural conditions. Specifically, the first one is to set the goal of cultivating field crops in the reclaimed land and the other is to evaluate the economic efficiency of utilizing the Hwaong reclaimed land as a farming complex. In chapter 2, this study outlined the prospect of the domestic and foreign supply and demand of farm products and indicated that international grain prices will keep rising for a while. In chapter 3, the development status of the reclaimed land and the methods of developing the upland soil are examined. A total of 38,588 hectares (in 2007) of the reclaimed land are available as a farming area. But the soil of the reclaimed land is unfavorable compared to a normal one physically and chemically. Therefore, in order to use the reclaimed land as farming fields, removing salt is necessary and desalination methods should be specified according to the purpose of farming. In chapter 4, the development status of the Hwaong reclaimed land and a general plan of the farming complex are investigated. Geographically being close to a harbor and a large consuming area, the reclaimed land has advantages in satisfying various development demands such as exporting farm products and producing high value-added ones. But as this area has sandy soil fine enough to have concerns over damages from being damp, artificial drainage facilities are needed. To develop a farming area in Hwaong reclaimed land, an orchard district is considered the most appropriate, followed by an export area of greenhouse vegetables and flowering plants. On top of arable crop area, a livestock area and a new renewable bio-district are the less suitable. In chapter 5, the economic efficiency of growing field crops in the reclaimed land is analyzed. First, the following shows estimated incomes that can be earned from cultivating different crops in the reclaimed land: a greenhouse floriculture area shows the highest income level with 163.4 million won per hectare, followed by a vegetable area with 102.7 million won per ha, a fruit growing area with 30.3 million won per ha, a food crop area with 9.8 million won per ha, a livestock area with 9.4 million won per ha, and a new renewable bio-district with 1.9 million won per ha. Second, the import substitution effect is projected to be the highest in an orchard district with 10.3 million won per ha, followed by a livestock area with 9.0 million won per ha, a new renewable bio-district with 4.2 million won per ha, and a food crop area with 2.8 million won per ha in that order. In chapter 6, amount of farm products and their amount of gross revenue are estimated with setting scenarios for the Hwaong reclaimed land. The highest income is acquired with scenario 3, considering the government policies with goals of food self sufficiency and the import substitution. In scenario 3, the guaranteed effects are 64.0 billion won of an annual farm household income (30.0 million won per ha) and 11.9 billion won of import substitution effect a year. Next, the variations in a farm household income and import substitution effects are considered depending on changing oil price and exchange rate. A farm household income decreases to 29.1 million won per ha with a 10% increase of oil price. It increases to 31.0 million won per ha if oil price drops by 10%. An additional amount of 1.2 billion won of import substitution effect is estimated when the import substitution amount increases to 13.1 billion won from 11.9 billion won with a 10% rise in both oil price and exchange rate. In summary, the analytical result showed that case of preserving the reclaimed land as a cultivated land, there were about 30 million won per ha of a farm household income and 5.3 million won per ha of import substitution effect. In order early achieve these goals, the followings are needed: First, keeping a farming area with a proper goal by publicizing the reclaimed farming land. Second, developing a field-crop producing area through the wide use of paddy fields and non-paddy fields. Third, a financial support to early stabilize farming practices in the reclaimed land.